Digital watermarking for digital media - Seitz, Juergen, 1968- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book discusses the new aspects of digital watermarking in a worldwide context. Approached not only from the technical side, but the business and legal sides as well, it discusses digital watermarking as it relates to many areas of digital media. Broad in its approach, the book provides a comprehensive overview useful to students in information technology, law, multimedia design, and economics, as well as artists, composers, lawyers, and publishers.